2018
DOI: 10.1016/j.celrep.2018.07.052
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Glutathione Redox Potential Are Linked to Aβ42-Induced Neurotoxicity

Abstract: Glutathione is the major low-molecular weight thiol of eukaryotic cells. It is central to one of the two major NADPH-dependent reducing systems and is likely to play a role in combating oxidative stress, a process suggested to play a key role in Alzheimer's disease (AD). However, the nature and relevance of redox changes in the onset and progression of AD are still uncertain. Here, we combine genetically encoded redox sensors with our Drosophila models of amyloid-beta (Aβ) aggregation. We find that changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 26 publications
3
23
0
Order By: Relevance
“…This is very important since dendritic spines are critical for synaptic function, including synaptic plasticity. Our results are in agreement with other studies that have shown the presence of increased S-glutathionylation of specific proteins in AD patients and mouse models (3,41,56,70). Studies with human postmortem AD frontal cortex tissues suggest that oxidative stress is an early feature and plays a critical role in AD…”
Section: Discussionsupporting
confidence: 93%
“…This is very important since dendritic spines are critical for synaptic function, including synaptic plasticity. Our results are in agreement with other studies that have shown the presence of increased S-glutathionylation of specific proteins in AD patients and mouse models (3,41,56,70). Studies with human postmortem AD frontal cortex tissues suggest that oxidative stress is an early feature and plays a critical role in AD…”
Section: Discussionsupporting
confidence: 93%
“…Notably, we demonstrate that the two cysteine residues of full-length tau act as key mediators of this phenotype, thereby identifying a novel cis -element governing the unconventional secretion of tau. Therefore, we suggest that the disease-associated redox disturbances in physiological cellular homeostasis might not only be a source of neuronal damage 78 , but they could in turn drive and promote the trans-cellular propagation of tau. Most importantly, such efforts for the in-depth characterization of the molecular mechanisms involved in the initiation and progression of the disease-related pathology will provide a stepping stone in the design of therapeutic approaches against neurodegeneration.…”
Section: Discussionmentioning
confidence: 98%
“…In humans, this decline occurs rapidly after age 45 (Imai and Guarente, 2014). The consequences of a decline in NAD + levels could be compromised mitochondrial energy production and impairment of the clearance of damaged mitochondria (Papa and Germain, 2017), along with a diminished capacity of the brain's response to oxidative stress (Kharrazi et al, 2008;Maruszak et al, 2011;Chico et al, 2013;Das et al, 2018;Liguori et al, 2018;Stapper and Jahn, 2018). States of intensive compensatory energy metabolism would lead to the production of ROS, which increase in an age-dependent fashion within the mitochondria (Kuka et al, 2013) with subsequent toxic effects damaging proteins, lipids, and DNA, eventually resulting in neuronal death.…”
Section: Identification Of Bioenergetic and Metabolic Alterations In Load Cells As A Function Of Cell Type Development Genetic Backgroundmentioning
confidence: 99%